Contrasting effects of mangroves and armoured shorelines on fish assemblages in tropical estuarine seascapes. (4th February 2019) - Henderson, Christopher J; Gilby, Ben L; Schlacher, Thomas A; Connolly, Rod M; Sheaves, Marcus; Flint, Nicole; Borland, Hayden P; Olds, Andrew D
Abstract: Coastal seascapes are composed of a diversity of habitats that are linked in space and time by the movement of organisms. The context and configuration of coastal ecosystems shapes many important properties of animal assemblages, but potential seascape effects of natural and artificial habitats on nearby habitats are typically considered in isolation. We test whether, and how, the seascape context of natural and urban habitats modified fish assemblages across estuaries. Fish were sampled with underwater videos in five habitat types (mangroves, rock bars, log snags, unvegetated sediments, armoured shorelines) in 17 estuaries in eastern Australia. Different habitats supported distinct fish assemblages, but the spatial context of mangroves and armoured shorelines had pervasive ecological effects that extended across entire estuaries. In most estuarine habitats, fish diversity and abundance was greatest when they were in close proximity of mangroves, and decreased due to the proximity of armoured shorelines. Many cities are centred on estuaries, and urban expansion is often associated with the fragmentation of mangrove forests. Our findings emphasize that these transformations of urban estuarine landscapes are likely to propagate to broader ecological impacts detectable in multiple habitats beyond mangrove forests.